Delocalized triplet state in porphyrin J-aggregates revealed by EPR spectroscopy. Issue 40 (9th October 2017) - Bolzonello, Luca; Albertini, Marco; Collini, Elisabetta; Di Valentin, Marilena
Abstract : In this work, the electronic structure of the triplet state of self-assembled J-aggregates of tetrakis(4-sulfonatophenyl)porphyrin (TPPS) has been characterized by means of time-resolved electron paramagnetic resonance spectroscopy. Abstract : In this work, the electronic structure of the triplet state of self-assembled J-aggregates of tetrakis(4-sulfonatophenyl)porphyrin (TPPS) has been characterized by means of time-resolved electron paramagnetic resonance spectroscopy. Several insights into the triplet properties of the aggregate have been gained through comparison with the corresponding monomeric unit in both free base and acidified forms. Molecular distortions in the monomeric acidified TPPS cause variation in its zero-field splitting parameters and a redirection of triplet spin sublevel activity. The aggregation process does not alter the mechanism of triplet state population compared to the acidified monomer but it is accompanied by a further reduction in the zero-field splitting parameter D, which is possibly indicative of the formation of a delocalized triplet state species. The detection of a long-lived spin-polarized radical species also proves polaron generation and movement to a trap site in the J-aggregates.